Information culture in the Maldives - Riyaz, A.; Smith, Kerry (Emerald, 2012)
This chapter discusses the Maldives information culture as observed and defined from the results of a research project undertaken as a Master of Philosophy at Curtin University in Australia. A survey of one rural Maldives community and one urban Maldives community collected data on their information use, access and awareness. Additional qualitative in-depth interviews with key information stakeholders in the Maldives sought supplementary information on the prevailing information situation. We present a conceptual model of the Maldives information culture including seven key elements: indigenous knowledge, ICTs, information literacy, research and publication, libraries and information services, mass media and information policies. The Maldives information culture is ‘paperless’, not in the modern online sense, but more in terms of the Maldives population's high reliance on verbal information interchange for their everyday information needs. In the Maldives, broadcast media and verbal information exchange predominate over print media. In the Maldives, reading as a leisure activity is present to some degree, but reading as an intellectual activity is limited. Libraries are not commonly used as an information source. Adoption of ICTs is swift and promising. However, even if the Maldives population is literate in the local language, a significant group lacks the English language literacy to benefit from the online information environment. There are no major differences in the use of information between the rural and urban community; the difference is in the level of access to information sources and the respondents' information literacy skills.